1991
DOI: 10.1002/dir.4000050306
|View full text |Cite
|
Sign up to set email alerts
|

Electronic shoppers and nonshoppers among videotex users

Abstract: This study investigated differences between electronic shoppers and nonshoppers among videotex users in terms of shopping orientations, videotex usages, and demographics. Data (N = 55 1 ) were collected via questionnaires sent to I ,ooO current subscribers to a major videotex company. By utilizing discriminant analysis, it was found that shopping orientations and videotex usages were successful overall in distinguishing electronic shoppers from nonshoppers. However, demographics were relatively unsuccessful. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…An early investigation (Korgaonkar and Moschis 1987) revealed that those who feel pressured for time favorably view Internet shopping. A few years later and contrary to expectations, Shim and Mahoney (1991) discovered that electronic shoppers were less time conscious than electronic nonshoppers. Later, Donthu and Garcia (1999) uncovered that Internet shoppers were less price conscious than nonshoppers, while 2 years earlier, price differences were not apparent (Kunz 1997).…”
Section: Related Literaturementioning
confidence: 73%
See 3 more Smart Citations
“…An early investigation (Korgaonkar and Moschis 1987) revealed that those who feel pressured for time favorably view Internet shopping. A few years later and contrary to expectations, Shim and Mahoney (1991) discovered that electronic shoppers were less time conscious than electronic nonshoppers. Later, Donthu and Garcia (1999) uncovered that Internet shoppers were less price conscious than nonshoppers, while 2 years earlier, price differences were not apparent (Kunz 1997).…”
Section: Related Literaturementioning
confidence: 73%
“…Studies investigating store characteristics included (1) time saving, (2) price, (3) convenience, (4) reduced risk, (5) comparative shopping, (6) customer service factors, and (7) variety of goods (Donthu and Garcia 1999;Korgaonkar and Moschis 1987;Kunz 1997;Mast, Oliver, and Shim 1991;Mast, Shim, and Morgan 1991;Shim and Mahoney 1991). An early investigation (Korgaonkar and Moschis 1987) revealed that those who feel pressured for time favorably view Internet shopping.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Although for many years it was posited that home shoppers were convenience oriented, research in recent years has revealed that some home shoppers are actually recreationally oriented (i.e., Gehrt and Carter 1992;Shim and Mahoney 1991). Thus, shoppers who have a home shopping orientation may actually think that shopping for groceries from home can be fun.…”
Section: Journal Of Food Pizoducts Marketingmentioning
confidence: 99%